Differences in mineral accumulation and gene expression profiles between two metal hyperaccumulators, Noccaea japonica and Noccaea caerulescens ecotype Ganges, under excess nickel condition. (3rd October 2021) - Enomoto, Takuo; Yoshida, Junko; Mizuno, Takafumi; Watanabe, Toshihiro; Nishida, Sho
ABSTRACT: Here we compare mineral accumulation and global gene expression patterns between two metal hyperaccumulator plants – Noccaea japonica, originating from Ni-rich serpentine soils, and Noccaea caerulescens (ecotype Ganges), originating from Zn/Pb-mine soils – under excess Ni conditions. Significant differences in the accumulation of K, P, Mg, B, and Mo were explained by the expression levels of specific transporters for each mineral. We previously showed that total Ni accumulation in the whole plant is higher in N. caerulescens than in N. japonica . Here we found a similar tendency for Fe under excess Ni; however, the expression of iron-regulated transporter 1 ( IRT1 ), which encodes the primary Fe uptake transporter and causes excess Ni uptake in Arabidopsis thaliana, was higher in N. japonica . NjIRT1 has a point mutation at Asp100, which is essential for Fe transport, and so might lack its Fe and possibly Ni transport function. Noccaea japonica might have lost its IRT1 function, which would prevent excess Ni uptake via IRT1 in Ni-rich soils, and come to rely on other transporters.